Extra-Adrenal Glucocorticoid Synthesis in the Intestinal Mucosa: Between Immune Homeostasis and Immune Escape - Ahmed, Asma; Schmidt, Christian; Brunner, Thomas (Frontiers in Immunology, 2019)
Glucocorticoids (GCs) are steroid hormones predominantly produced in the adrenal glands in response to physiological cues and stress. Adrenal GCs mediate potent anti-inflammatory and immunosuppressive functions. Accumulating evidence in the past two decades has demonstrated other extra-adrenal organs and tissues capable of synthesizing GCs. This review discusses the role and regulation of GC synthesis in the intestinal epithelium in the regulation of normal immune homeostasis, inflammatory diseases of the intestinal mucosa, and the development of intestinal tumors.